Quantifying the potential impact of a green supporting factor or brown penalty on European banks and lending. Issue 3 (8th July 2019) - Thomä, Jakob; Gibhardt, Kyra
Abstract : Purpose: The European Parliament and Commission are considering introducing a green supporting factor (GSF) or brown penalty (BP) for capital reserve requirements. This paper aims to estimate the potential impact such a policy intervention may have on both capital reserves of European banks and the cost and availability of capital to "green" and "brown" investments. Design/methodology/approach: The paper draws on the existing empirical and theoretical literature on the impacts of changes to capital reserve requirements on the real economy. It applies these estimates on the particular policy intervention currently being discussed at EU level to estimate the potential range of impacts on the cost of capital – measured in basis points – and the availability of capital – measured in per cent changes to lending. Findings: A GSF would have a limited effect on overall capital requirements of banks compared to a BP – given the larger universe of assets on which such a penalty would be applied. The estimated effect is a reduction in capital requirements associated with a GSF of around €3-4bn based on baseline "green" definitions. In terms of cost of capital, the paper estimates a reduction of 5 to 26 basis points for green projects (with inverse expected effects for a BP). In terms of availability of capital, analysing a BP suggests a potential reduction in lending to brown assets of up to 8 per cent. Originality/value: The paper provides direct evidence, with the first quantitative analysis of the potential impact of the current policy proposition discussed at EU-level.